Sharenting and the extended self: self-representation in parents' Instagram presentations of their children. (2nd January 2022) - Holiday, Steven; Norman, Mary S.; Densley, Rebecca L.
ABSTRACT: The sharenting practice, or the sharing of one's parenting and children online, has become a popular topic of critical focus that decries it as an exploitative disregard for children's privacy and rights. The practice is performed, however, by a population (i.e., parents) that is generally inclined to protect its children, raising the present research question of whether sharenting could be alternatively guided by self-presentational goals. Guided by the theoretical notion of the extended self, the present study qualitatively examines parents' Instagram posts using constant comparative analysis to identify how parents self-present in their sharenting posts. The results identify three self-presentational categories that illustrate how parents' social media posts that depict a parent–child relational identity may actually be intended representations of the parent's self. Implications for theory are discussed, as well as practical implications for the appropriate management of parents' identities in a manner that respects children's rights and privacy.